Initial growth and physiological indexes of Fig accessions in active germoplasm bank - Fontanetti Rodrigues, Maria Gabriela [UNESP]; Arruda Ferreira, Antonio Flavio; Honorato Monteiro, Lais Naiara [UNESP]; Santos, Tatiane Paes dos [UNESP]; Manzani Lisboa, Lucas Aparecido; Monteiro de Figueiredo, Paulo Alexandre [UNESP] (Soc Brasileira Fruticultura, 2019)
Fruit growing has become an important alternative economic strategy for the social reproduction of small rural producers. Fig (Ficus carica L.) is a fruit of great world importance, and can be used as a new source of agricultural variability, adding advantages, both economically and socially. In addition, the characterization of active germplasm banks of the genus Ficus becomes an important research line for culture improvement, and it is necessary to gather information, mainly in relation to its genetic variability, so that adequate propagation and management projects are carried out. Therefore, the aim of this work was to establish and characterize an active germplasm bank of fig tree by means of the morphophysiological descriptors of 45 fig accessions, with a randomized complete block design at the Faculty of Agrarian and Technological Sciences, Campus of Dracena, FCAT / UNESP. To do so, the biometric features of re-growth, relative growth rate, plant height and morphophysiological characteristics of the best performance accessions during their vegetative development were evaluated. It could be concluded that most accessions presented good adaptation to the implantation region, especially accessions 18, 28, 29, 30 and 31, which were more promising.
Keywords: Ficus carica L.; conservation of genetic resources; morphophysiology